ANALISIS PERBANDINGAN KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR ENERGI BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS - Amri Aziz Mustifa; Navisatul Muna; Nur Hafidz; Darmawan Darmawan; Achmad Jufri (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to determine the financial performance of companies in the energy sector consisting of PT Buana Lintas Lautan Tbk., PT Energi Mega Persada Tbk., and PT Harum Energy Tbk. This research is a type of quantitative research using secondary data obtained from financial statements for the 2011-2021 period. Analysis in this research is using a financial ratio of companies consisting of liquidity ratio (current ratio, quick ratio, and cash ratio), solvability ratio (debt to Asset and debt to equity), and profitability ratio (return of assets and return of equity). The results of the analysis based on the liquidity ratio in 2011-2020 show that the company has been able to meet its short-term obligations by using its current assets, but for PT Buana Lintas Lautan and PT Energi Mega Persada in 2021, it experienced a significant decline due to a decrease in current assets and an increase in short-term loans. Then based on the analysis of solvability shows the financing of the company’s debts is quite good because the company can close total debts with assets owned. Based on the profitability ratio indicates the use of profits over equity and profits on assets experiencing fluctuations every year, which means the ability of the company in producing net profits from sales, capital, and asset is unstable.